A Unique and Species-Rich Assemblage of Freshwater Glassfishes (Teleostei: Ambassidae: Dapalis) from the lower Oligocene of the Central Paratethys with the Description of Four New Species - Harald Ahnelt; Katarina Bradić-Milinović (Taxonomy)
We describe four new species of the fossil genus Dapalis (Ambassidae), Dapalis absconditus sp. nov., Dapalis octospinus sp. nov., Dapalis parvus sp. nov. and Dapalis quintus sp. nov., based on articulated skeletons with otoliths in situ from a freshwater habitat of the lower Oligocene of Raljin/Strelac (Serbia). Besides in body shape (e.g., body length, body depth, head length, preanal length), the species differ in morphological characters like, e.g., the serration of the preopercle, the length of the first two spines of the first dorsal and the anal fin and the morphology of the sagittal otoliths (e.g., ratio of otolith height to otolith length, ratio of otolith width to otolith length). Together with D. pauciserratus, also described from Raljin, these four species represent the most species-rich assemblage of freshwater Dapalis known so far. The compartmentalization of the internal structure of the spines reveals the close relationship of Dapalis and extant Ambassidae. Additionally, we discuss a new character from the ventral field of the otolith, a ventral depression, only found in species from Raljin. This new character is unique among the European Dapalis species and allows us to separate these five species into two species groups.